2007
DOI: 10.1007/s11914-007-0026-9
|View full text |Cite
|
Sign up to set email alerts
|

B vitamins, homocysteine, and bone disease: Epidemiology and pathophysiology

Abstract: Observational studies indicate that mildly elevated homocysteine is a strong risk factor for osteoporotic fracture, yet there is no clear biologic mechanism for an effect of homocysteine on bone. The association could instead be attributed to B vitamins (folate, vitamin B(12), vitamin B(6)), as low levels of these nutrients are the primary determinants of homocysteine and may be associated with lower bone quality. Discovery of a direct effect of homocysteine or B vitamins on bone would be important in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 47 publications
0
16
0
2
Order By: Relevance
“…These findings are in agreement with those of a recent study of 1,550 old American subjects, which concluded that neither serum nor red blood cell folate was related to BMD or osteoporosis [10], possibly because of a higher mean age and higher mean plasma folate concentration. However, several studies [5,23] have found a significant positive correlation of folate with BMD. The direct association between plasma tHcy and plasma folate with BMD is not well documented except in reports describing the development of osteoporosis in patients with inherited classical homocystinuria [25].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…These findings are in agreement with those of a recent study of 1,550 old American subjects, which concluded that neither serum nor red blood cell folate was related to BMD or osteoporosis [10], possibly because of a higher mean age and higher mean plasma folate concentration. However, several studies [5,23] have found a significant positive correlation of folate with BMD. The direct association between plasma tHcy and plasma folate with BMD is not well documented except in reports describing the development of osteoporosis in patients with inherited classical homocystinuria [25].…”
Section: Discussionmentioning
confidence: 96%
“…Osteoporosis is a well-recognized feature of homocystinuria, and many large general population cohort studies demonstrated positive relations between circulating tHcy levels and osteoporosis and hip fracture risk [3][4][5][6][7]. These findings raised the hope of reducing the burden of an enormous public health problem through B-vitamin therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A candidate for increased oxidative stress may be hyperhomocysteinemia. A moderately increased plasma homocysteine (Hcys) level in the general population may indicate a fracture risk that is independent of BMD [4,142]. McKusick first proposed that hyperhomocysteinemia might interfere with normal enzymatic collagen cross-link formation [143], and this proposed mechanism was confirmed indirectly in homocystinuric patients.…”
Section: Collagen Cross-links In Osteoporosismentioning
confidence: 99%
“…Homocysteine metabolism requires the presence of vitamin B 6 , vitamin B 12 , and folate; deficiency of any of these vitamins can lead to elevations in plasma homocysteine. Homocystinuria, a rare autosomal-recessive disorder causing elevated plasma homocysteine levels and severe vaso-occlusive disease, is associated with osteoporosis [67]. Hyperhomocysteinemia in the general population has been associated with a two-to fourfold increase in fracture risk [68,69], but studies of homocysteine and BMD are inconsistent [67].…”
Section: B Vitaminsmentioning
confidence: 99%